Assessment of resistance mechanisms to fall armyworm, Spodoptera frugiperda in tropical maize inbred lines - Ovide Nuambote-Yobila; Bruce, Anani Yaovi; Gerphas Ogola Okuku; Marangu, Charles; Makumbi, Dan; Beyene, Yoseph; Nzola-Meso Mahungu; Prasanna, Boddupalli M.; Marion-Poll, Frédéric; Calatayud, Paul-André (MDPI, 2023)
The fall armyworm (FAW), Spodoptera frugiperda, a pest of maize native to the Americas first reported in West and Central Africa in 2016, severely threatens maize production and food security in Sub-Saharan Africa. Native genetic resistance is one of the best methods of control of insect pests as it is contained in the seed making it more amenable for use by farmers compared to other interventions and it is also compatible with other integrated pest management (IPM) options. An intensive screening against FAW was carried out by artificial infestation in greenhouse conditions in Kenya between 2017 and 2018 on about 3000 inbred lines available in the germplasm collection of the International Maize and Wheat Improvement Center (CIMMYT). Among these lines, only four showed to be resistant to FAW, but the mechanisms of resistance are not yet known. The objective of this study was to determine the resistance mechanisms specifically non-preference and antibiosis to S. frugiperda in these four selected resistant inbred lines. The studies were conducted under laboratory and net house conditions in Kenya from April 2020 to November 2021. Non-preference was assessed estimating the feeding preference by counting the number of FAW neonates found on each leaf portion, silk portion and grain using binary and multiple choice methods under laboratory conditions, while antibiosis was assessed through the relative growth rate (RGR) and developmental time of FAW larvae on leaves, silks and grains under both laboratory and net house conditions. Among the four resistant maize inbred lines tested, two, namely CML71 and CKSBL10008, exhibited the highest level of antibiosis resistance on leaves. Under laboratory conditions, the larval RGR reduced from 13 mg/d on the most susceptible line to 8 mg/d on CML71. CML71 also showed a good non-preference on leaves compared to other tested lines. Only 6% of neonates choose to feed on CML71 whereas more than 10% choose to feed on the other lines (and 15% on the most susceptible) in multiple choice tests. The non-preference for feeding and lower RGR of larvae on CML71 suggest a biochemical involvement resistance to FAW. Through this study, CML71 is revealed as a highly promising line for use in breeding for native genetic resistance to FAW in tropical maize.